Vascular disease burden, outcomes and benefits with empagliflozin in heart failure: insights from the EMPEROR-reduced trial - Khan, Muhammad Shahzeb; Anker, Stefan D.; Filippatos, Gerasimos; Ferreira, João Pedro; Pocock, Stuart J.; Januzzi, James L.; Chopra, Vijay K.; Piña, Ileana L.; Böhm, Michael; Ponikowski, Piotr; Verma, Subodh; Brückmann, Martina; et al. (Journal of cardiac failure, 2023)
Background - The presence of ischemic heart disease impacts prognosis in patients affected by heart failure and reduced ejection fraction (HFrEF). It is not well known how the extent of vascular disease impacts prognoses and responses to therapy in this setting. - Methods - In this post hoc analysis of the EMPEROR-Reduced trial, outcomes and the effects of empagliflozin, were assessed in study participants according to the extent (none vs mono1 vs poly [≥ 2] vascular bed) of vascular disease. Vascular disease was defined as investigator-reported coronary artery disease (CAD), peripheral artery disease (PAD) and cerebrovascular disease at baseline. Cox proportional-hazards models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). Incidence rates are presented per 100 person-years (py) of follow-up. - Results - Of the 3730 study participants enrolled, 1324 (35.5%) had no vascular disease, 1879 (50.4%) had monovascular disease, and 527 (14.1%) had polyvascular disease. Participants with polyvascular disease tended to be older and male and to have had histories of hypertension, diabetes and smoking. In the placebo arm, a significantly higher risk for cardiovascular death existed in those with polyvascular disease (HR 1.57, 95% CI1.02, 2.44, compared to those with no vascular disease). In adjusted analysis, the benefit of empagliflozin in cardiovascular death or hospitalization due to HF, HF hospitalization, cardiovascular death, renal composite endpoint, estimated glomerular filtration slope changes, and health status scores were seen across the 3 groups (interaction P > 0.05 for all) but were attenuated in those with polyvascular disease. Adverse events were higher in those with polyvascular disease, but no major differences were noted between empagliflozin or placebo assignment in the 3 groups. - Conclusion - In patients with HFrEF, the extent of vascular disease is associated with the risk for adverse cardiovascular outcomes. Empagliflozin offers cardiovascular and renal benefits in HFrEF across the extent of vascular disease, but this benefit is attenuated in those with polyvascular disease.
Online verfügbar: 8. August 2023, Artikelversion: 10. Oktober 2023
Gesehen am 19.09.2024